Isbat Nikah among Muslim Communities in Aceh: Legal Compliance or Reactive Administrative Necessity - Mansari, Mansari; Hasballah, Khairuddin; Devy, Soraya; Fauziati, Fauziati; Sahara, Siti (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2026)
This study analyzes the implementation of isbat nikah (marriage legalization) among Muslim communities in Aceh, examining whether it is driven by genuine legal awareness or merely administrative necessity—often used reactively to obtain birth certificates, inheritance rights, or access to social assistance. The central issue arises when isbat nikah is perceived merely as a shortcut to legalize previously unregistered marriages, rather than as a legal process reflecting compliance with the state’s normative legal framework. The purpose of this research is to examine the meaning of isbat nikah in the context of legal consciousness within society and to identify its legal position as an instrument for resolving socio-religious problems. The research employs a normative juridical method with both conceptual and statutory approaches to examine the legal basis of isbat nikah as regulated in the Compilation of Islamic Law, Law No. 1 of 1974 on Marriage, and the procedural provisions of the Religious Courts. Data analysis was conducted descriptively and analytically through the examination of legal norms and the interpretation of empirical practices evolving within society. The findings reveal that the practice of isbat nikah is predominantly motivated by administrative needs rather than genuine legal awareness. Muslim communities tend to interpret isbat nikah as a legal mechanism to obtain state recognition for marriages already valid under religious law, with its primary function serving administrative purposes. The legal position of isbat nikah plays a crucial role in resolving socio-religious issues stemming from unregistered marriages and in providing legal protection for women and children. However, public compliance with isbat nikah remains reactive and administrative in nature, driven by practical needs rather than a normative understanding of legal obligation. [Penelitian ini menganalisis pelaksanaan isbat nikah di kalangan masyarakat Muslim di Aceh yang dilakukan atas dasar kesadaran hukum atau kepentingan administratif sebagai respons reaktif untuk pengurusan akta kelahiran anak, warisan, atau kepentingan administrasi lainnya. Permasalahan utama muncul karena isbat nikah dimaknai semata sebagai jalan pintas legalisasi perkawinan yang sebelumnya tidak tercatat, bukan sebagai proses hukum yang mencerminkan kepatuhan terhadap norma hukum negara. Tujuan penelitian ini adalah untuk menganalisis makna isbat nikah dalam konteks kesadaran hukum masyarakat serta mengidentifikasi posisi hukum isbat nikah sebagai instrumen penyelesaian masalah sosial keagamaan. Metode penelitian yang digunakan adalah yuridis empiris dan yuridis normatif dengan pendekatan konseptual dan perundang-undangan untuk menelaah dasar hukum isbat nikah yang diatur dalam Kompilasi Hukum Islam, Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, serta ketentuan peradilan agama. Analisis data dilakukan secara deskriptif dan analitis melalui penelaahan norma hukum dan interpretasi terhadap praktik empiris yang berkembang di masyarakat. Hasil penelitian menunjukkan bahwa makna pelaksanaan isbat nikah lebih didorong oleh kebutuhan administratif daripada kesadaran hukum yang sejati. Isbat nikah dimaknai masyarakat sebagai sarana hukum untuk memperoleh pengakuan negara atas perkawinan yang telah sah secara agama, dengan fungsi utama sebagai pemenuhan kebutuhan administratif. Posisi hukum isbat nikah berperan penting dalam menyelesaikan problem sosial keagamaan akibat perkawinan tidak tercatat serta memberikan perlindungan hukum bagi perempuan dan anak. Ketaatan masyarakat terhadap isbat nikah masih bersifat reaktif dan administratif, dipengaruhi oleh kebutuhan praktis, bukan oleh kesadaran hukum yang lahir dari nilai normatif.]